Modeling Overcharge at Graphite Electrodes: Plating and Dissolution of Lithium. Issue 1 (4th September 2019) - Baker, Daniel R.; Verbrugge, Mark W.
Abstract : We derive and implement a set of equations that can be used to describe overcharge of a lithium ion cell, which can result in lithium (Li) plating on the graphite electrode. Graphite electrodes are the current material of the choice for the negative electrode (anode on discharge). We add two theoretical developments to published models to address Li plating. First, the existing models are not well-posed in terms of handling the Li deposition and dissolution electrochemical reactions. Second, the plated Li can interact directly with vacant sites in the graphite, which has not been treated in the literature, and which impacts the system response. With the inclusion of these new theoretical developments, and the use of our recently developed multi-site, multi-reaction (MSMR) formulation, we demonstrate the utility of the overcharge model and simulate relatively fast charging and discharging of a graphite electrode (i.e., at the 1C rate, yielding about 1 hour to fully charge or discharge the electrode) with a single-particle representation.